Evaluation of Nonlinear Behavior of Dual Steel Frame-Shear Wall System by a Group of Real Earthquakes - Reza Bemanian (Iranian Society of Structrual Engineering (ISSE), 2016)
Dual system of steel moment frame and steel plate shear wall has many advantages in comparison to the other systems. Since the last four decades the dual system has been used more frequently in new and existing structures. the steel shear wall has many advantages such as high ductility, strength, stiffness and it has light weight, it consequent reduce lateral forces and time efficiency in contracture procedure. The aim of this study is to evaluate the seismic performance of the dual steel frame steel plate shear wall system in comparison with the moment resisting frame using nonlinear dynamic analysis. A dual System of Steel Moment frame and steel Plate shear walls system and a moment resisting frame is chosen a frame of four stories building were designed by used existing code. The height of each floor is 3.5 m. Seismic behavior of frame evaluate using nonlinear dynamic analysis. For this purpose a set of seven earthquake ground motions were appropriately selected and applied to the systems. Interstory drift ratio, input energy, distribution frames responses in height were compared for the systems under two different hazard level of ground motion and the results were analyzed.